Comparison of Batch and Repeated Batch Operation of Lactulose Synthesis with Cross-Linked Aggregates of Bacillus Circulans β-galactosidase - Vera-Vera, C (Elsevier Ltd, 2020)
Synthesis of lactulose with crosslinked aggregates of Bacillus circulans β-galactosidase (CLAGs) has been compared in batch and repeated-batch operation for the first time. The effect of the type of the precipitating agent and its concentration, the crosslinker concentration and the time of crosslinking were evaluated for their effect on the parameters: immobilization yield, specific activity and thermal stability of the biocatalysts. The type and concentration of the precipitating agent were the variables that produced a significant variation in the immobilization parameters of the biocatalyst. CLAGs were obtained with a specific activity of 7790 IUH⋅g−1 at an immobilization yield of 46.2 % using 50 % v/v of propanol as precipitating agent, 5.5 gglutarldehyde gprotein −1 for crosslinking and 1 h of crosslinking time. This biocatalyst was more stable than the free enzyme with a stabilization factor of 11.3 h at 50 °C. Highest yield of lactulose synthesis with CLAGs was 0.42 g g−1 for a fructose/lactose molar ratio of 8. Repeated-batch operation allowed a significant increase in lactulose production per unit mass of biocatalyst and in cumulative productivity with respect to batch operation, yielding an efficiency of biocatalyst use of 2.43 kglactulose gbiocatalyst protein −1. © 2020 Elsevier Ltd